Harmonisasi Tradisi Akkudu-Kudu Dan Maqashid Syariah Dalam Mengoptimalkan Penerimaan Zakat Di Sulawesi Selatan - Ali, Ali Mumin (Yayasan Darussalam Patalassang, 2025)
Zakat as a fiscal instrument is very important in overcoming socio-economic disparities and can improve people's welfare. The purpose of this research is to analyse the concept of akkudu-kudu tradition with maqashid sharia principles and its implementation in Indonesia. The research method used is descriptive qualitative with a literature study approach. The results showed that the concept of akkudu-kudu tradition can be integrated with maqashid sharia principles to optimise zakat revenue in South Sulawesi. The cultural approach involving traditional leaders and community leaders, public awareness of the importance of zakat has increased so that participation in paying zakat has become wider. In addition, the application of maqashid sharia principles in zakat distribution, such as economic empowerment and transparency, has strengthened the impact of zakat in reducing poverty and improving the welfare of mustahik. This harmonisation not only enriches the practice of zakat management, but also creates a model that can be adopted in other areas to achieve more equitable social and economic justice.